Fires at the wildland-industrial interface. Is there an emerging problem? - Planas, Eulàlia; Paugam, Ronan; Àgueda, Alba; Vacca, Pascale; Pastor, Elsa (Fire safety journal, 2023)
Over the past years, wildfires have raged with unprecedented intensity across the world, becoming a growing problem, as weather conditions conductive to wildfire ignition and spread will increase in frequency and severity worldwide. This, coupled with a growing human expansion, leads to an increase in wildfire risk and in the threat to wildland-urban interface (WUI) communities. Commonly, definitions for WUI areas consider homes, commercial facilities, office and public buildings. This excludes industrial installations, where wildfires can trigger accidents or cascading events leading to extremely dangerous situations for the population causing enormous economic losses. In this paper, the problem associated to the wildland-industrial interface (WII) is analyzed. A methodology to obtain a global WII map is described, and the first WII maps for Europe and Asia are provided. Results show that, in Europe, 2.5% of the land and 6% of vegetated areas are WII, while in Asia these are respectively 0.24% and 0.5%. An analysis of how wildfire triggered industrial accidents can be considered when performing quantitative risk assessments (QRA) in industrial sites is also performed, identifying the current state of the art and research gaps, with the aim of helping industry, public authorities and policy makers, for better accident prevention, preparedness and response. •A full resolution WII map for the whole world is provided for the first time.•In Europe, Germany is the country with the largest WII area (3.3 Mha).•In Asia, China and Japan are the countries with the largest WII areas (3.5 and 0.8 Mha).•Industries at the WII having hazardous materials need to consider wildfire risk.•The inclusion of wildfire risk into Quantitative Risk Assessment is analyzed.